World Bank Policy Research : A Historical Overview - Dethier, Jean-Jacques (2012)
The World Bank is a leading intellectual institution on development. It is a world leader in analytical studies in areas including poverty measurement, delivery of social services, impact evaluation, measurement of development outcomes, international trade and migration. It is also a leader in development data, including the Living Standard Measurement Surveys; the enterprise surveys, and the International Price Comparison Project. World Bank research is resolutely empirical and policy oriented. By both learning from past policies and operations and thinking critically about future policies, research plays a critical role in the formulation of policy advice to developing countries. This paper reviews the intellectual and institutional forces that have shaped research at the World Bank since the latter started lending to developing countries in the early 1950s. It provides an overview of the shifts in development economics that have influenced Bank research and briefly surveys the changes in research organization, structure and approach. The first section, after a short introduction, examines the shifts in positive and normative views about development during the past half century that have influenced Bank thinking. The Bank itself has been an active participant in the rise and fall of long-lived development dogmas about the nature of development; the most appropriate policies and actions for achieving it; and the respective roles of government and markets. The second section examines how the World Bank has adapted its organization to keep abreast of emerging issues and produce relevant policy research of good quality. On the one hand, the Bank has experienced several reorganizations that have affected the research unit(s) as well as its relationship with operational units. On the other hand, the Bank s research units themselves have been reorganized at several junctures, leading to new priorities and new means of achieving them.